National Woman's Party records - National Woman's Party; DuPont, Jean Kane Foulke, 1891-1975.; Hadley, Lucia Hanna; Ogle, Dora G.; Paul, Alice, 1885-1977.; Pollitzer, Anita, 1894-1975.; West, Helen Hunt, 1892-
Correspondence, minutes of meetings, reports, administrative files, financial and legal records, printed material, newspaper clippings, photographs, and other records documenting the organization's efforts to promote congressional passage of both the nineteenth amendment to the Constitution guaranteeing women the right to vote and the Equal Rights Amendment. Subjects include legal, social, and economic status of women in the U.S. and around the world, the party's publications Suffragist and Equal Rights, attempts to promote jury service for women, cooperative efforts with other woman's organizations and with the international women's movement, the treatment of imprisoned suffragists, and the International Woman Suffrage Alliance.
Also includes records (1938-1958) of the World Woman's Party and papers of party members and officials including Jean Kane Foulke DuPont, Lucia Hanna Hadley, Dora G. Ogle, Alice Paul, Anita Pollitzer, and Helen Hunt West.
Selected photographs also available through the Library of Congress Web site.
Microfilm edition available, in part
Photostats, in part.
Microfilm 18,276-97P (Suffrage Years) produced from originals in the Manuscript Division.
Photostats produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Keywords: United States; International Woman Suffrage Alliance; World Woman's Party; Equal rights; Suffragist; Constitutional amendments -- United States; Equal rights amendments -- United States; Suffragists -- United States -- History; Jury duty; Women -- Economic conditions; Women -- United States -- Economic conditions; Women -- Legal status, laws, etc; Women -- Legal status, laws, etc. -- United States; Women -- Social conditions; Women -- United States -- Social conditions; Women -- Societies and clubs; Women -- Suffrage -- Periodicals; Women -- Suffrage -- United States; Women's rights; Women's rights -- International cooperation